2021
DOI: 10.3168/jds.2020-18527
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of microorganisms in Kazakhstan koumiss and their application in preparing cow-milk koumiss

Abstract: Koumiss is a type of famous fermented mare milk and considered an important nutritious beverage in central Asian countries. However, the production of koumiss cannot meet public demand in the market due to availability of mare milk. In the present study, 52 lactic acid bacteria and 20 yeast strains from traditional homemade Kazakhstan koumiss were isolated and identified. The isolates were used in a trial that included fermented cow milk, and the flavor profiles, color, and taste to determine their contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 56 publications
1
10
0
1
Order By: Relevance
“…Initially, and due to a lack of study, the fermentation of mare milk was the result of uncontrolled processes that did not guarantee the quality of the product, leading to sanitary or sensory defects [3]. Indeed, the composition of the microbiota of the initial mare milk is variable and can differ depending on the region and season of qymyz production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, and due to a lack of study, the fermentation of mare milk was the result of uncontrolled processes that did not guarantee the quality of the product, leading to sanitary or sensory defects [3]. Indeed, the composition of the microbiota of the initial mare milk is variable and can differ depending on the region and season of qymyz production.…”
Section: Introductionmentioning
confidence: 99%
“…The studies available on qymyz revealed that the main microorganisms responsible for the fermentation were lactic acid bacteria (LAB) and yeasts [4]. The authors mainly focused on the identification of microorganisms [3,5,6]. Rakhmanova et al [3] found 52 lactic acid bacteria and 20 yeasts.…”
Section: Introductionmentioning
confidence: 99%
“…Однако сезонность его производства -один из факторов, ограничивающих его широкое применение в практике фтизиатрии. В связи с вышеизложенным востребованы исследования, направленные на разработку технологий производства кумысных напитков, приближенных по составу к функциональным продуктам на основе кобыльего молока [10]. В научно-исследовательской лаборатории Башкирского института технологий и управления «МГУТУ им.…”
Section: результаты и обсуждениеunclassified
“…In addition, RSM makes it possible to evaluate the simultaneous interaction of these variables and model the selected response parameters; likewise, the predicted data is usually consistent with the experimental data [ 30 ]. In recent years, due to these benefits, RSM has become the most popular method for optimization processes [ 31 , 32 , 33 ]. Agarwal et al [ 34 ] produced polylactic acid-based nanofibers and investigated the impact of various electrospinning conditions using the RSM method.…”
Section: Introductionmentioning
confidence: 99%